INVESTIGATION OF SOME PROPERTIES OF WOOD-POLYMER MATERIAL BASED ON MODIFIED UREA-FORMALDEHYDE RESIN (Innovation in Woodworking Industry and Engineering design, 2026)
Wood processing is related to the release of large amounts of waste, such as wood dust, sawdust and others. In order to their utilization perspective direction is the wood-polymer materials production, which can be applied in many industries. In the present study some physical and mechanical properties of wood-polymer material based on modified urea-formaldehyde resin with chlorine-containing polymers were investigated. The obtained results showed that the increase of chlorinated paraffin content leads to an improvement in all investigated physical and mechanical properties.